Comparison of deuterium incorporation and mass isotopomer distribution analysis for measurement of human cholesterol biosynthesis - Marco Di Buono; Peter J.H. Jones; Louis Beaumier; Linda J. Wykes (Journal of Lipid Research, 2000)
To compare endogenous cholesterol biosynthesis measured by deuterium incorporation (DI) and mass isotopomer distribution analysis (MIDA), cholesterol fractional and absolute synthetic rates were measured simultaneously by both techniques under identical physiological conditions. Twelve subjects (22 to 39 years of age) underwent a dual stable isotope protocol, involving oral deuterium oxide administration and measurement of incorporation of deuterium into cholesterol coincident with constant infusion of sodium [1-13C]acetate and measurement of the mass isotopomer distribution pattern of newly synthesized cholesterol. Synthesis was determined over 24 h with a 7-h feeding period. Both methods yielded similar measurements of fractional cholesterol synthesis (7.8 ± 2.5% day−1 for DI vs. 6.9 ± 2.2% day−1 for MIDA). Correlation of fractional synthesis across techniques was strong (r = 0.84, P = 0.0007). Absolute synthesis rates were also not different at 24 h (13.4 ± 4.3 mg kg−1 day−1 for DI vs. 11.9 ± 3.6 mg kg−1 day−1 for MIDA, r = 0.79, P < 0.002). We conclude that despite different assumptions and analytical requirements, deuterium incorporation and MIDA yield similar rates of cholesterogenesis in humans when measurements are made over 24 h. The decision as to which method to adopt depends on available clinical and analytical facilities. —Di Buono, M., P. J. H. Jones, L. Beaumier, and L. J. Wykes. Comparison of deuterium incorporation and mass isotopomer distribution analysis for measurement of human cholesterol biosynthesis. J. Lipid Res. 2000. 41: 1516–1523.